Anlysis of Anies Rasyid Baswedan’s Political Rhetoric In The 2017 Jakarta Gubernatorial Election (Case Study of the 2017 Jakarta Gubernatorial Debate) - Prasetyo, Hari; Mustikasari, Eka; Martins, Felismino; Hutapea, Edison Bonartua (FISIP Universitas Bung Karno, 2024)
AbstractRhetoric is closely related to a person's ability to give a speech or speak in front of an audience. In the contestation of the 2017 DKI Jakarta Gubernatorial Election, candidates get a special opportunity, especially for candidates who are not favored to win the contestation such as Anies Rasyid Baswedan, who can attract sympathy and political support from the public through effective rhetoric skills. This study analyzes how Anies Rasyid Baswedan in the 2017 DKI Jakarta Regional Election contestation used Aristotle's rhetoric concept and invitation rhetoric in the Cagub-Cawagub debate organized by the DKI Jakarta KPUD so that he could come out as the winner of the Pilkada. This type of research uses a qualitative method with a rhetorical analysis approach. Data collection was carried out using digital trace documentation collection techniques obtained from video recordings on the CNN Indonesia youtube channel. The results showed that Anies Rasyid Baswedan effectively utilized Aristotle's rhetorical concepts in the aspects of ethos, pathos and logos to gain the support of Jakarta residents. Anies Baswedan in the debate successfully implemented an approach strategy to the audience by using the basic concepts of invitation rhetoric theory which emphasizes the principle of equality, attitude to universal values (immanent value) and attitude of self-determination. This succeeded in attracting sympathy and political support from DKI Jakarta residents to vote for him so that he could come out as the winner of the 2017 DKI Jakarta Pilkada.Keywords: Political Persuasion, Rhetoric Politics, Aristotle's Rhetoric, Invitation Rhetoric, Political Communication